2017
DOI: 10.1002/aoc.3700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solvent coordination on the structure of β‐diketone‐based vanadyl complexes and assessment of in vitro antidiabetic activity and cytotoxicity

Abstract: The physicochemical properties, thereby the biological efficacy, of metal complexes are affected based on their structure and geometry that vary in the presence of coordinating and non-coordinating solvents. To investigate this, in the present work, we synthesized three hitherto unreported β-diketone-based oxovanadium(IV) complexes, namely [VO(tfdmh) 2 ] (tfdmh =1,1,1-trifluro-5,5dimethyl-2,4-hexanedione), [VO(dmh) 2 ] (dmh = 2,2-dimethyl-3,5-hexanedione) and [VO(dbm) 2 ] (dbm = 1,3-diphenylpropane-1,3-dione),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…The cytotoxic activity, of VO (IV) complexes ( 1–3 ), is evaluated for in vitro anti‐tumor activity against two different human cell lines: (i) HepG‐2, and (ii) MCF‐7, by using vinblastine and colchicine as a reference compounds (referring to Figures 9 and 10). [ 47–49 ] Table 4 represents summary of the calculated values of the IC 50 by using Equation , for the tested VO (IV) complexes. These results revealed that the complex 1 (IC 50 = 115 ± 6.9, and 169 ± 8.7 μg/mL) is exhibiting non‐toxicity against the two cell lines HepG‐2 and MCF‐7, respectively, as compared to the Colchicine (IC 50 = 10.6 ± 0.…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxic activity, of VO (IV) complexes ( 1–3 ), is evaluated for in vitro anti‐tumor activity against two different human cell lines: (i) HepG‐2, and (ii) MCF‐7, by using vinblastine and colchicine as a reference compounds (referring to Figures 9 and 10). [ 47–49 ] Table 4 represents summary of the calculated values of the IC 50 by using Equation , for the tested VO (IV) complexes. These results revealed that the complex 1 (IC 50 = 115 ± 6.9, and 169 ± 8.7 μg/mL) is exhibiting non‐toxicity against the two cell lines HepG‐2 and MCF‐7, respectively, as compared to the Colchicine (IC 50 = 10.6 ± 0.…”
Section: Resultsmentioning
confidence: 99%